Afghanistan Drug Insights 2024 - United Nations Office on Drugs; Crime (United Nations, 2025)
The Afghanistan Drug Insights 2024 is a set of three reports that provide latest data and in-depth analysis on aspects of the evolving drug situation in Afghanistan. Opium production in Afghanistan remains low for the second consecutive year, with production at 433 tons in 2024, confirmed new estimates from the UN Office on Drugs and Crime (UNODC). Although this figure represents a 30 per cent increase from 2023, production still remains 93 per cent below 2022 levels, when the de facto authorities began enforcing a country-wide drug ban.